(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The aim of this research is to examine the impact of adopting International Financial Reporting Standard (IFRS 6) on enhancing the informational content of financial statements in Iraqi oil companies engaged in exploration and evaluation activities. This is achieved by analyzing the 2023 financial data of a selected oil exploration company as a case study and measuring the informational content using the (Kothari et al. 2005) model, based on the values of discretionary accruals as an indicator of the quality of informational content. The higher the discretionary accruals, the lower the quality of the financial statements’ informational content, and vice versa. Additionally, the research relies on the use of (Excel and SPSS V.27) software for extracting the results related to the practical aspect of the study. The researchers concluded several key findings, the most important of which are: the complexity of the oil industry and the differences in accounting practices contributed to a negative impact on the financial statements, as it exposed the comparability feature to risk on one hand, and hindered users’ ability to understand and make informed investment decisions on the other. Furthermore, the issuance of (IFRS 6) introduced a new perspective in accounting for exploration and evaluation expenditures in financial reporting, which contributed to making financial statements clearer and more understandable for users. The researchers also provided a set of recommendations, the most important of which is that oil companies, especially in exploration and evaluation activities, should adopt standardized accounting practices in preparing financial statements to enable users to better understand and compare them. This can be achieved by adopting (IFRS 6), as this adoption is considered an important step in improving the treatment of exploration and evaluation expenditures in financial statements.